The Influence of Using Audio Visual Media on the Poetry Writing Skills of Class VIII Mts Students. Muhammadiyah 22 Padangsidimpuan - dewi, shoufi nisma (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
AbstractThis research aims to determine the effect of using audio visual media on the poetry writing skills of class VIII MTs students. Muhammadiyah 22 Padangsidimpuan Academic Year 2024-2025. This research method uses a qualitative method with a descriptive approach. The population in this study were all students in class VIII MTs. Muhammadiyah 22 Padangsidimpuan has 72 students, consisting of 24 students in class VIII-A, 24 students in VIII-B, and 24 students in VIII-C. The research sample used was from class VIII-C, totaling 24 students. The data collection technique uses a multiple choice test consisting of 10 questions and 5 description questions. The research results show differences in the average values for variables X and Y. The average value for variable X is 78.75, while the value for the test results for variable Y is 86.25. These results show that there is a significant influence from the use of audio-visual media on poetry writing skills, in other words Ha is accepted and Ho is rejected. Keywords: Audiovisual, Writing, Poetry.